Optimization of Pitavastatin Calcium and Micronized Fenofibrate Bi-layer Tablets Using Quality by Design - Park, Jun Woo; Song, Il Dae; Kang, Jae Seon; Kim, Kang Min (Indian Journal of Pharmaceutical Education and Research, 2026)
Background and Purpose: This study aimed to develop bilayer tablets containing pitavastatin calcium and micronized fenofibrate. Materials and Methods: For optimization of manufacturing based on preliminary formulation research, a 24+3 full factorial Design of Experiments (DoE) study was conducted to elucidate the effects of four factors (Ludipress®, crospovidone, Polyethylene Glycol (PEG) 6000, main compression) influencing tablet Critical Quality Attributes (CQAs) such as hardness, friability, assay and dissolution rates at pH 1.2 and pH 4.5 with 2.88% Sodium Lauryl Sulfate (SLS). Analysis of variance was conducted using Design Expert software to evaluate the 4 responses (hardness, friability, assay and dissolution). Results: Ludipress®(p=0.0212), crospovidone (p<0.0001), PEG 6000 (p=0.0011) and main compression (p=0.0314) significantly affected friability. Hardness was also affected by crospovidone (p=0.0208). Dissolution rates at pH 4.5 with 2.88% SLS were affected by the interaction between crospovidone and PEG 6000 (p=0.0417). These results indicate that the optimized ranges of Ludipress® (4.55-10.59%), crospovidone (7.36-8.94%), PEG 6000 (8.06-9.09%) and main compression (1903-2158.41 kgf ) had a positive influence on the tablet CQAs. Conclusion: Process optimization of the bilayer tablets was conducted using a four-factor, two-level, full-factorial design. This enabled the rapid evaluation and identification of critical process variables, facilitating the successful evaluation of bilayer tablets with excellent quality using the quality by design approach.
Keywords: Design of experiment; Micronized fenofibrate; Pita vastatin calcium; Quality by design.